2010
DOI: 10.1007/s11104-010-0449-4
|View full text |Cite
|
Sign up to set email alerts
|

Soil carbon and nitrogen mineralization following deposition of insect frass and greenfall from forests under elevated CO2 and O3

Abstract: Elevated CO 2 and O 3 alter tree quality and the quality of herbivore inputs, such as frass, to forest soil. Altered quality or quantity of herbivore inputs to the forest floor can have large impacts on belowground processes. We collected green leaves and frass from whitemarked tussock moth caterpillars from aspen-birch stands at the Aspen Free Air CO 2 Enrichment (FACE) site near Rhinelander, WI, USA. Small or large quantities of frass, greenfall, or a 1:1 ratio of frass and greenfall were added to microcosms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 60 publications
(72 reference statements)
0
8
0
Order By: Relevance
“…However, the N input can lead to a cascade of soil chemical reactions on which fungi and bacteria are distinctly adapted and differ in their reaction time [36]. Additionally, it has been observed that only moderate to high amounts of organic input lead to changes in soil microbial population growth [37]. The lower defoliation intensity of the pine-tree lappet (50%) compared to the nun moth outbreak (80%) may, therefore, explain the differences in the bacterial and fungal population sizes in our study.…”
Section: The Soil Fungal and Bacterial Population Size Responds To Inmentioning
confidence: 99%
“…However, the N input can lead to a cascade of soil chemical reactions on which fungi and bacteria are distinctly adapted and differ in their reaction time [36]. Additionally, it has been observed that only moderate to high amounts of organic input lead to changes in soil microbial population growth [37]. The lower defoliation intensity of the pine-tree lappet (50%) compared to the nun moth outbreak (80%) may, therefore, explain the differences in the bacterial and fungal population sizes in our study.…”
Section: The Soil Fungal and Bacterial Population Size Responds To Inmentioning
confidence: 99%
“…The easy soluble structure of insect feces, with high amounts of labile C and extractable N, can facilitate nutrient release in soils [15][16][17]. Therefore, decomposition processes in the course of defoliations may be enhanced [10,18], thereby triggering CO 2 emissions from forest soils [15,19,20]. In contrast, findings from xylophagous insects (compared to phytophagous insects) showed contradictory results.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, forest soils seem to have a certain resistance to biotic disturbances. This may explain why effects of organic input from insect outbreaks on microbial respiration or nitrogen immobilization in soils are often only detectable at relatively high levels of defoliation (>70%) [19,29]. Nevertheless, the effects of forests pests on greenhouse gas emissions are not sufficiently understood to predict environmental effects.…”
Section: Introductionmentioning
confidence: 99%
“…These materials fall throughout the growing season and are of higher nutritional quality than senesced leaf litter (hereafter, ‘leaf litter’) deposited at the end of the growing season (Hunter, ; Lovett et al ., ). This pulse of labile, nutrient‐rich material moves through numerous avenues in forest ecosystems, including uptake by trees and assimilation into canopy foliage (Frost & Hunter, ), immobilization by microbial communities (Christenson et al ., ; Hillstrom et al ., ), and export from the system via surface and ground water (Hunter et al ., ; Frost & Hunter, , ; Townsend et al ., ). The timing and chemical composition of herbivore‐mediated material fluxes (hereafter, ‘herbivore fluxes’) have a strong impact on forest nutrient cycles (Hunter, ; Lovett et al ., ), even when herbivores occur at endemic population levels (Hunter et al ., ), and especially in highly nutrient‐limited forests (Metcalfe et al ., ).…”
Section: Introductionmentioning
confidence: 99%